PENGARUH MODEL GAME BASED LEARNING BERBASIS GIMKIT TERHADAP HASIL BELAJAR IPAS DI SDN PAKIS V SURABAYA - Dwi Agus Tina Ningrum; Suryandari, Savitri; Larasati, Diyas Age (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This research was motivated by the low learning outcomes of students in the IPAS subject due to learning activities that were still dominated by teacher explanations, causing students to be less active in the learning process. This study aims to determine the effect of the Game Based Learning model assisted by Gimkit on the learning outcomes of fourth-grade students at SDN Pakis V Surabaya. This research used a quantitative approach with a quasi-experimental method using a nonequivalent control group design. The research sample consisted of an experimental class and a control class, with 30 students in each class. Data were collected through learning outcome tests in the form of pretest and posttest. The research instruments were tested for validity and reliability before being used. Data analysis was conducted using prerequisite tests, including normality and homogeneity tests, followed by hypothesis testing using the independent sample t-test. The results showed that there was a significant difference in students’ learning outcomes between the class that applied the Game Based Learning model assisted by Gimkit and the class that used conventional learning. The implementation of the Game Based Learning model assisted by Gimkit had a positive effect on improving students’ IPAS learning outcomes. Therefore, the Game Based Learning model assisted by Gimkit can be used as an alternative learning model to create active, innovative, and enjoyable learning activities.